"Being Able to Listen Makes Me Feel More Engaged": Best Practices for Using Podcasts as Readings. (October 2021) - Oslawski-Lopez, Jamie; Kordsmeier, Gregory
We investigate student listening compliance, preference for audio versus print content, and exam performance when professionally produced podcasts are assigned as "readings" and provided in both audio and print formats. Listening/reading compliance for the assigned podcasts was high compared with figures reported in previous research. The most popular format for accessing the content was listening, followed by reading, followed by doing both. Most students perceived their selected mode made it easier to focus and comprehend. Many students switched their mode of access between assignments, and some mentioned that having options was important. Students who read podcast transcripts were more likely to answer exam questions correctly than those who only listened to the podcasts, a finding likely tied to multitasking behavior reported by listeners. Our findings suggest instructors should provide students access to both podcast audio and transcripts and explicitly teach students how to best engage with podcast content.